Monday

April 21, 2014

April 21, 2014

Posted by **Jon** on Tuesday, May 20, 2008 at 1:02pm.

x=2y

x^2+2y^2=18

(2y)^2+2y^2=18

4y^2+2y^2=18

6y^2=18

y^2=3

y=+-3

x=2(+-3)

x=+-23

(+-2sqrt3,+-sqrt3)

2)Simplify, (d/(d^2-9)) + (5/(2d+6))

[d / (d^2 - 9)] + [5 / (2d + 6)]

= [d / (d - 3) (d +3)] + [5 / 2 (d + 3)]

= [2d + (5 {d - 3})] / [2 (d + 3) (d - 3)]

= [2d + 5d - 15] / [2 (d + 3) (d - 3)]

= (7d - 15) / [2 (d + 3) (d - 3)]

= (7d - 15) / (2d^2 - 18)

**Related Questions**

Mathematics - Trigonometric Identities - Let y represent theta Prove: 1 + 1/tan^...

linear algebra - Use an inverse matrix to solve each system of linear equations...

linear algebra - Use an inverse matrix to solve each system of linear equations...

linear algebra - Use an inverse matrix to solve each system of linear equations...

Algebra - Find the exact solutions of the systems of equation x^2+2y^2=18 and x=...

Expressions help - I have no idea on how to do this equation please help me. ...

math-calculus - (5y)/(6y^2-7y-3)+(4y-3)/(2y^2-15y+18)consider nonpermissible ...

algebra - how do I do this Solve for x. 3x 2y = 6 Add 2y to both sides and ...

Algebra 1 - REINY, Thank you for your answer and the answer is obviously correct...

Algebra - I need help on this one too, please. Solve for X. 3x-2y=6 I got x=6+2y...